MORPHOLOGIC FEATURES OF THE RETINAL PIGMENT EPITHELIUM AND ASSOCIATED CHORIORETINAL CHARACTERISTICS IN EYES WITH EARLY AGE-RELATED MACULAR DEGENERATION AND SUBRETINAL DRUSENOID DEPOSITS. Issue 4 (April 2020) - Jang, Sungmin; Park, Seo Yeon; Ahn, So Min; Hwang, Soon-Young; Kim, Seong-Woo; Oh, Jaeryung; Yun, Cheolmin
Abstract : Purpose: To investigate the features of the retinal pigment epithelium (RPE) on optical coherence tomography in eyes with early age-related macular degeneration with subretinal drusenoid deposit. Methods: We classified the eyes into three types: nonundulating RPE, undulating RPE, and wedge-shaped RPE. We compared the retinal vessel densities, retinal thickness, and choroidal thickness of a 3-mm-diameter zone. Results: We classified 33, 27, and 20 as nonundulating RPE, undulating RPE, and wedge-shaped RPE eyes, respectively. The vascular densities of the superficial and deep capillary plexus showed differences; nonundulating RPE group (23.93 ± 2.26% and 23.54 ± 1.78%), undulating RPE group (22.29 ± 2.80% and 21.94 ± 2.42%), and wedge-shaped RPE group (21.93 ± 2.70% and 20.63 ± 2.42%, P = 0.010 and P < 0.001). The mean retinal thickness and choroidal thickness were also different, nonundulating RPE group (298.26 ± 13.81 µ m and 180.08 ± 55.49 µ m), undulating RPE group (285.29 ± 21.88 µ m and 148.45 ± 55.08 µ m), and wedge-shaped RPE group (274.86 ± 20.62 µ m and 135.75 ± 39.77 µ m) ( P = 0.001 and P = 0.007). Conclusion: Altered features of the RPE on optical coherence tomography may indicate advancement in disease and be part of an overall degeneration process in these eyes. Abstract : Chorioretinal characteristics varied according to the morphology of retinal pigment epithelium on optical coherence tomography in eyes with early age-related macular degeneration and subretinal drusenoid deposit. Retinal pigment epithelial degeneration may be part of an overall degeneration process in these eyes.Supplemental Digital Content is Available in the Text.